Prevalence of Chest Pain, Depression, Somatization, Anxiety, Global Distress, and Substance Use among Cardiac and Pulmonary Rehabilitation Patients - Madan, Alok; Borckardt, Jeffery J.; Serber, Eva R.; Balliet, Wendy E.; Galloway, Sarah K.; Taylor, Marian; Edwards-Hampton, Shenelle A.; Yeager, Brooke; Clair, Mark (Pain Research and Treatment, 2012)
Psychosocial factors of cardiovascular disease receive a preponderance of attention. Little attention is paid to psychosocial factors of pulmonary disease. This paper sought to describe psychosocial characteristics and to identify differences between cardiac and pulmonary patients entering a phase II rehabilitation program. Parametric and nonparametric analyses were conducted to examine scores on the Brief Symptom Inventory-18 (BSI-18) and the CAGE-D, administered at entry as standard clinical care. Participants were 163 cardiac and 63 pulmonary patients. Scores on the BSI-18 “chest pain” item indicated that more cardiac patients report chest pain than pulmonary patients. Among all subjects, chest pain ratings were positively related to anxiety, depression, and global distress. There were equivocal proportions of anxiety and somatization in patient groups. Pulmonary patients were more likely to endorse clinically significant levels of depression and global psychological distress than cardiac patients. Cardiac patients were significantly more likely to screen positively on the CAGE-D than pulmonary patients. Findings show a relationship between symptoms of chest pain and psychological distress. Despite equivalent proportions of anxiety and somatization between groups, a greater proportion of pulmonary patients reported symptoms of depression and global psychological distress, while more cardiac patients reported chest pain. Further research is needed to examine this paradigm.